Peripheral neuropathy in COVID-19 is due to immune-mechanisms, pre-existing risk factors, anti-viral drugs, or bedding in the Intensive Care Unit - FINSTERER, Josef; SCORZA, Fulvio Alexandre; SCORZA, Carla Alessandra; FIORINI, Ana Claudia (Arquivos de Neuro-Psiquiatria, 2021)
Background: This mini-review aims to summarize and discuss previous and recent advances in the clinical presentation, pathophysiology, diagnosis, treatment, and outcome of SARS-CoV-2-associated peripheral neuropathies. Methods: Literature review. Results: Altogether, 105 articles about SARS-CoV-2-associated neuropathy describing 261 patients were retrieved. Peripheral neuropathy in patients with COVID-19 is frequent and predominantly due to immune mechanisms or neurotoxic side effects of drugs used to treat the symptoms of COVID-19 and, to a lesser extent, due to the compression of peripheral nerves resulting from prolonged bedding in the Intensive Care Unit (ICU) and pre-existing risk factors such as diabetes. SARS-CoV-2 does not cause viral neuropathy. Neurotoxic drugs such as daptomycin, linezolid, lopinavir, ritonavir, hydro-chloroquine, cisatracurium, clindamycin, and glucocorticoids should be administered with caution and patients should be appropriately bedded in the ICU to prevent SARS-CoV-2-associated neuropathy. Patients with Guillain-Barré syndrome (GBS) benefit from immunoglobulins, plasma exchange, and steroids. Conclusions: Neuropathies of peripheral nerves in patients with COVID-19 are frequent and mostly result from immune mechanisms or neurotoxic side effects of drugs used to treat the symptoms of COVID-19 and, to a lesser extent, from the compression of peripheral nerves due to prolonged bedding on the ICU. SARS-CoV-2 does not cause infectious neuropathy.
Keywords: Guillain-Barre Syndrome; Polyneuropathies; Drug-Related Side Effects and Adverse Reactions; Mononeuritis Multiplex; SARS-CoV-2